THE IMPLEMENTATION OF GENRE – BASED APPROACH FOR THE TEACHING OF ENGLISH AT SMPN 01 WONOSARI KLATEN - WULANDARI, FITASARI (2011)
This research is aimed at describing the teaching learning process at the secondyear of SMPN 01WonosariKlaten using Genre-based Approach, specifically on finding the procedures of the process of teaching English using Genre-based Approach,the activities used in teaching English applying Genrebased Approach, the problemsin implementing of Genre-basedApproach, and the way used by the teachers to overcome the problemin implementing the GenrebasedApproach in the process of teaching English.In this research, the writer uses an ethnographic research which describes theimplementation of Genre-based Approach in teaching of English. The data compriseactivities in teaching of English, information from English teacher, headmaster, and the students, and curriculum in SMPN 01WonosariKlaten. The methods ofcollecting are observation, interview and documentation. The procedures for analyzingdata are reducing, display, and verification.The result shows that in classroom procedure, there are three patterns; BKOF-MOT-ICOT-JCOT, BKOF-MOT-ICOT, and BKOF-MOT-JCOT. In every stage, there are many activities in classroom done by theteacher. The activities in BKOF are asking question and giving explanation. In MOT, theteacher gives the same text to discuss. In JCOT, the activity is group discussion. And theactivities in ICOT are giving the task in the classroom and giving task as homework.The research also shows the problems faced by theteacher. The problems are the student’svocabulary, difficulty in managing the class,and the student’s different capability.The stages ofthegenre theory used by the teacher in the implementation of Genre-based Approach is not always complete and in line with the theory. Keyword: Genre-based Approach, teaching of English.